Rick and Morty, Meeseeks, P.I. - Stresing, Fred (Oni Press, 2024)
"The remote to the interdimensional cable box has gone missing . . . and everyone is a suspect! Desperate to find it before Rick can berate him, Jerry enlists the help of Meeseeks, P.I., and the two set off to retrieve the remote. Their search quickly turns up more than they bargained for, attracting seedy goons and assassins, and unraveling a massive interdimensional cable conspiracy hidden right underneath their noses!"--Publisher's description.